Evaluation of Aeromonas hydrophila outer membrane protein deletion strains in response to environmental stresses - LI Zeqi; WANG Yuqian; LI Xiaoyan; LIN Xiangmin; YUAN Jun (浙江大学学报. 农业与生命科学版)
In order to evaluate systematically the biological functions of outer membrane proteins (OMPs) under environmental stresses, we selected Aeromonas hydrophila ATCC 7966 as the research object, and constructed 33 OMP deletion strains to determine their growth status under the stress conditions of osmotic pressure, metal ions, H2O2 and pH. The results showed that the AHA_0461 and AHA_4275 (encoding TonB protein family) knockout strains grew better than the wild type strain under the osmotic pressure stress. The AHA_2282 (encoding an unknown functional protein) knockout strain grew weakly under the metal ion stresses, while ΔAHA_0904 strain grew better under the osmotic pressure stress. The AHA_2145 (encoding long-chain fatty acid transporter) knockout strain grew weakly under the H2O2 and metal ion stresses. The growth of AHA_1279, AHA_1281 (encoding OmpA family protein) and pilQ, AHA_0569 (encoding secretin family protein) knockout strains was weaker than the wild type strain under the H2O2 stress. It was suggested that these OMPs may play important roles in response to environmental stresses. These results may highlight a comprehensive understanding of the physiological functions of bacterial OMPs under different environmental stresses in the future, and provide possible targets for the prevention and control of this pathogen.